2016
DOI: 10.12973/eurasia.2017.00651a
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Waves Conceptual Survey: An Analysis of University Students’ Performance, and Recommendations for Instruction

Abstract: The Mechanical Waves Conceptual Survey (MWCS), presented in 2009, is the most important test to date that has been designed to evaluate university students' understanding of four main topics: propagation, superposition, reflection, and standing waves. In a literature review, we detected a significant need for a study that uses this test as an assessment tool and presents a complete analysis of students' difficulties on the test. This article addresses this need. We administered the MWCS at a private university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…At the end of the research, it was determined by simulation programs that students' misconceptions on mechanical waves decreased. Consequently, as Barniol and Zavala (2017) suggest, literature shows us that students have misconceptions and incomplete knowledge of mechanical waves. It is noteworthy that studies on mechanical waves mostly focused on determining students' conceptual understanding of the process.…”
Section: Teaching Mechanical Wavesmentioning
confidence: 99%
“…At the end of the research, it was determined by simulation programs that students' misconceptions on mechanical waves decreased. Consequently, as Barniol and Zavala (2017) suggest, literature shows us that students have misconceptions and incomplete knowledge of mechanical waves. It is noteworthy that studies on mechanical waves mostly focused on determining students' conceptual understanding of the process.…”
Section: Teaching Mechanical Wavesmentioning
confidence: 99%
“…During the third STEM activity (design of string and wind instruments), students also demonstrated some difficulties to identify the factors that affect pitch in a string and to conclude that the pitch generated by air blown across the top end of a bottle will be higher when it contains a greater volume of water, which is quite similar to some results obtained by Barniol and Zavala (2017). When engaged in the design of a string instrument, one group of students (G3) failed to distinguish the concept of sound from the concept of sound intensity (volume), which is in line with the work of Özkan and Selçuk (2013), whose findings demonstrated that most students considered that those concepts were the same.…”
Section: Sound Attributesmentioning
confidence: 53%
“…Sound waves. The analysis of the fourth activity worksheets on the topic of sound waves also showed G1 misunderstanding about the previous parameters (amplitude and frequency) mentioned before, which is one of most common errors concerning sound variables (Barniol & Zavala, 2017). Some PSTs (G1 and G3) considered that the velocity of sound dependende on frequency and amplitude.…”
Section: Sound Attributesmentioning
confidence: 84%
“…Tongchai et al (2009) developed a conceptual understanding test for mechanical waves which had questions on conceptual understanding questions on standing waves. Then, Barniol and Zavala (2017) applied this to students taking the "Fluids, waves, and thermodynamics" class, and tried to determine the questions and concepts that students had difficulty with. At the end of this study, it was revealed that students had difficulty in conceptual understanding standing waves and that there is a need for further studies to analyze this difficulty in detail.…”
Section: The Aim Of the Studymentioning
confidence: 99%